Electrochemical Synthesis of Nitric Acid from Nitrogen Oxidation. Issue 12 (27th January 2022) - Wang, Yuting; Li, Tieliang; Yu, Yifu; Zhang, Bin
Abstract: Nitric acid is widely applied in agriculture and industry. The present manufacturing process via a combination of the Haber–Bosch process and the Ostwald oxidation process is accompanied by massive energy consumption and greenhouse gas emissions. The direct electrocatalytic nitrogen oxidation reaction (NOR) to nitric acid is a promising alternative, especially when it is driven by renewable energy sources. The standardization of performance evaluation is the prerequisite for the design and synthesis of efficient electrocatalysts for NOR. In this context, this Minireview first discusses the history of the development of HNO3 manufacturing and the possible reaction mechanisms for electrocatalytic NOR. Then, a strict protocol for electrochemical NOR experiments is recommended. Finally, general research targets associated with techno‐economic analysis, challenges, and prospects for NOR are summarized for future studies. Abstract : The electrocatalytic nitrogen oxidation reaction (NOR) has drawn widespread attention due to its potential for the green synthesis of nitric acid. Since a prerequisite for the favorable development of this emerging field is the rational testing of NOR performance, a recommended protocol is presented in this Minireview. In addition, possible reaction mechanisms and future perspectives, as well as challenges related to NOR, are discussed.